К 70-летию профессора Валерия Дмитриевича Работягова - Ходосовцев, А. Е.; Бойко, М. Ф.; Орел, Т.И.; Исиков, В.П. (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
К 70-летию профессора Валерия Дмитриевича Работягова